Vehicle recognition and notification system for security personnel - Ng, Han Inn (2019)
Developing a mobile object recognition device with limited compute resources to inform the end user of any vehicle and allowing them to make an informed decision. The device is used to test the ability to recognise incoming vehicle approaching the carpark barrier with the intention of replacing the need of an attendant to operate the barrier.